Anthropometric Investigations in the Institute of Industrial Design - Batogowska, Anna (Anthropological Review, 1987)
The article discusses the necessity of moving anthropometry to new research fields following from the requirements of technics: It has been shown that with the help of classical reference systems and methods used in classical anthropometry one can obtain only a small amount of information useful for designers and constructors. The connection of anthropometry with technics requires that, next to the basic investigations carried out according to the generaly accepted principles, methods and measurement points, some specialist«: investigations fulfilling the conditions of usability for the practical application should be carried out. Special examinations are carried out according to new methods, measurement points and reference systems. The anthropometric studies for the needs of technics are carried out in the Laboratory of Ftincional Antrhopometiy, Institute of Industrial Design in Warsaw, with the help of specially designed and manufactured prototypical measurement apparatus.